Eunuchs and the Postgender Jesus: Matthew 19.12 and Transgressive Sexualities - Hester, J. David (Journal for the study of the New Testament, 2005)
The eunuch of Mt. 19.12 has long been viewed as a symbol of chastity and celibacy. However, a study of ancient perspectives on eunuchs reveals a highly sexed and morally dubious ‘third type of human’ embodying the worst fears of masculine vulnerability and sexual transgression. Many early Christians interpreted Jesus’ instruction literally, imitating their counterparts in other religious traditions who employed castration as an expression of religious devotion. This created difficulties for certain church leaders concerned with appealing to (aristocratic) male converts, and the effort to transform the eunuch into a symbol of masculine askesis was never an easy one.In this article I problematize the ‘celibate’ eunuch, exploring implications that a symbol of sexual transgression would have for current discussion regarding the proscription of homosexuality in the Church. Fundamental to understanding Mt. 19.12 is the explicit rejection of the heterosexist binary paradigm for understanding the role and importance of sex, sexuality and sexed identity in the ‘kingdom of heaven’.